Emerging structural biology of TRPM subfamily channels. (May 2019) - Chen, Yixiang; Zhang, Xu; Yang, Tingting; Bi, Ruixue; Huang, Zhanmei; Ding, Hao; Li, Jian; Zhang, Jin
Graphical abstract: Fig. 1 Structures of TRPM channels. (A) Cartoon representation of a nTRPM2 (n: Nematostella vectensis) protomer. (B) Cartoon representation of a h TRPM4 ( h: Homo sapiens ) protomer. (C) Cartoon representation of a m TRPM7 ( m: Mus musculus ) protomer. (D) Cartoon representation of a f TRPM8 ( f: Ficedula albicollis ) protomer. (E) Comparison of n TRPM2 (green), h TRPM4 (cyan), m TRPM7 (magentas) and f TRPM8 (slate). Highlights: TRPM channels play a significant role in cell development and relevant diseases. Members of TRPMs display considerable structural and functional homology. There are now four unique TRPM structures, which have presented many unprecedented structural findings. The comparison between each new structure of TRPM channels brings many new biological insights. Abstract: TRPM family (Transient receptor potential channels, M for melastatin) is a group of intrinsic plasma membrane ion channels which are widely expressed throughout human body. It has been identified as a potent entry point of working desperate diseases out in a new way with newfangled ideas and safer technological means. In our review, we discussed the common and unique properties of TRPM family with the elaborate narrate in their overall structures, different states and the underlying activation mechanism. Thus, this review can help to consummate the limited work of TRPM family and provide novel therapeutic targets of certain diseases.